2017
DOI: 10.1021/jacs.7b08012
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Basis for Deuterium Labeling of Fat and NADPH

Abstract: Much understanding of metabolism is based on monitoring chemical reactions in cells with isotope tracers. For this purpose, 13C is well suited due to its stable incorporation into bio-molecules and minimal kinetic isotope effect. For redox reactions, however, deuterium tracing can provide valuable additional information. To date, studies examining NADPH production with deuterated carbon sources have failed to account for roughly half of NADPH’s redox active hydrogen. Here we show that the missing hydrogen is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 31 publications
4
100
0
Order By: Relevance
“…We next aimed to directly monitor G6PD mediated hydride transfer to NADPH. Specifically, we traced the transfer of deuterium from [1- 2 H]glucose, via glucose-6-phosphate, to the NADPH’s active hydride ( Figure 1d ) 24 . Consistent with this labeling arising primarily from the G6PD reaction, G6PD knockout cells demonstrated a nearly complete loss of active hydride labeling ( Figure 1f ).…”
Section: Resultsmentioning
confidence: 99%
“…We next aimed to directly monitor G6PD mediated hydride transfer to NADPH. Specifically, we traced the transfer of deuterium from [1- 2 H]glucose, via glucose-6-phosphate, to the NADPH’s active hydride ( Figure 1d ) 24 . Consistent with this labeling arising primarily from the G6PD reaction, G6PD knockout cells demonstrated a nearly complete loss of active hydride labeling ( Figure 1f ).…”
Section: Resultsmentioning
confidence: 99%
“…In normal physiological conditions, 4% of NADH in pancreas is labeled by 2 H-serine infusion. The real contribution of serine catabolism is, however, larger, as labeling is limited by the deuterium kinetic isotope effect (slower reactivity of deuterated, compared to unlabeled, methylene-THF) and by 1 H-2 H exchange between NADH and water (Ducker et al, 2016;Schmidt et al, 2000;Wiberg, 1955;Zhang et al, 2017). The magnitude of both of these effects is on the order of 2-fold (perhaps substantially larger for 1 H-2 H exchange), suggesting that ~20% or more of pancreas NADH is made by serine catabolism, with serine's contribution less in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…1A). While the raw extent of malate labeling was small, due to tracer loss via H-D exchange, even modest 2 H labeling is often biologically meaningful (Zhang et al, 2017).…”
Section: Serine Catabolism Feeds Nadh In Vivomentioning
confidence: 99%
“…The redox-active H on NADPH is moderately acidic and can potentially exchange with water. Indeed, labeling experiments with 2 H2O in different transformed human cell lines revealed that ∼40% to ∼70% of the redox active hydrogen of NADPH comes from water (48). It was shown that NADPH-dependent flavin enzymes such as glutathione reductase that hold the hydride in a N-H bond instead of a C-H bond catalyze this exchange.…”
Section: Discussionmentioning
confidence: 99%